Analysis of paint traces to determine the ship responsible for a collision - H. Lee (Nature Portfolio, 2021)
Abstract Although there have been many instances of ship collision at sea in recent times, not much research has been conducted on the topic. In this study, paint from an actual site of ship collision was collected and analyzed as evidence. The amount of evidence collected from the ships involved in the collision is either small or has inconsistent morphology. In addition, the contaminants and samples are often mixed in this evidence, making its analysis difficult. Paint traces of the damaged ship and the ship suspected to be responsible for the collision were compared through scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM–EDS), attenuated total reflection–Fourier transform infrared spectroscopy (ATR–FTIR), thermogravimetry (TG) and derivative thermogravimetry (DTG), and pyrolysis–gas chromatography/mass spectrometry (Py–GC/MS) analyses. The ship responsible for the collision could be identified by characterization and by performing a comparative analysis of the extracted paint. Among the methods used in this study, Py–GC/MS can sensitively analyze even similar paints, and identified styrene and phthalic anhydride as the most prominent components of the paint used as evidence. The results obtained can be used to investigate the evidence collected from collision sites and to determine the ship responsible for the collision.